NILAI PENDIDIKAN KARAKTER NOVEL RUMAH DI SERIBU OMBAK KARYA ERWIN ARNADA - Sukirno Sukirno (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2016)
Abstract: This Research is aimed is to describe the instrinsic elements and values of character education found in Erwin Arnada’s Rumah Seribu Ombak. This data of this research is taken the novel entitled Rumah Seribu Ombak while the object of this study is the educational value of the characters of the novel. The tecknique of collecting data is by using libraly research in which the researcher himself is the maun instrument of the research aided by data recording card, while the technique of data analysis is content analysis technique. The results of this research are as follows: (1) an intrinsic element of Erwin Arnada’s Rumah Seribu Ombak is the friendship, the main character of the novel is Samihi who is very tolerant to others, while the minor characters are Wayan Manik, Haji Aminullah and Syamimi. The plot of the novel is flash-bach and the setting consists of the setting of time, place, and social atmosphere. (2) The value of character education found in Rumah Seribu Ombak are religious values, honesty, tolerance, diciline, hard work, creativity, independence, democratic, curiosity, love of the homeland, appreciating the achievements, friendship/sense of comunication, love of peace, love of reading, environmentalcare, social care, and responsibility. Keywords: the educational value of the character, Rumah Seribu Ombak Abstrak: Tujuan penelitaian ini adalah untuk mendeskripsikan: unsur intrinsik dan nilai pendidikan karakter novel Rumah di Seribu Ombak karya Erwin Arnada. Sumber data penelitian ini novel Rumah di Seribu Ombak karya Erwin Arnada. Objek penelitian ini adalah nilai pendidikan karakter yang terdapat dalam novel Rumah di Seribu Ombak. Teknik pengumpulan data digunakan teknik pustaka, instrumen utamanya adalah peneliti dibantu kartu pencatat data, sedangkan teknik analisis data digunakan teknik analisis isi. Berdasarkan hasil penelitian disimpulkan: (1) Unsur intrinsik novel Rumah di Seribu Ombak karya Erwin Arnada bertema persahabatan, tokoh utamanya Samihi yang memiliki karakter sangat toleran kepada orang lain. Adapun tokoh pendampingnya yaitu Wayan Manik, Haji Aminullah, dan Syamimi. Novel tersebut beralur mundur. Latar cerita meliputi latar tempat, waktu, sosial dan suasana. (2) Nilai pendidikan karakter novel Rumah di Seribu Ombak terdiri atas nilai religius, jujur, toleransi, disiplin, kerja keras, kreatif, mandiri, demokratis, rasa ingin tahu, cinta tanah air, menghargai prestasi, bersahabat/komunikatif, cinta damai, gemar membaca, peduli lingkungan, peduli sosial, dan tanggung jawab. Kata kunci: nilai pendidikan karakter, novel Rumah di Seribu Ombak